Musculoskeletal discomfort associated with remote work conditions of professors during the COVID-19 confinement in Colombia - Margarita Portilla Diaz; Santiago Goméz Velásquez; Clara Rocío Galvis López; Sandra Ortegón Ávila (Christian Journal for Global Health, 2023)
Remote working led to organizational and adaptive processes at workplaces, with ergonomic and psychosocial risk factors being present that could be associated with musculoskeletal symptoms. This study identifies musculoskeletal discomfort developing in this setting among university professors working remotely because of the COVID 19 pandemic, evaluates risk levels associated with this workplace, and estimates the need for remedial action. The study had a quantitative, observational, cross-sectional design and used a secondary source of information. Statistical analysis used Jamovi software. Professors reported primarily neck discomfort, followed by discomfort in the dorsal or lumbar region. A statistically significant association was found between the category “requires action” and those who reported dedication to occupational activities more than eight hours per day. Work at home conducted by the professors is related to discomfort on the neck and dorsal or lumbar region. Risk assessment shows that, under these conditions, the professors required timely action to avoid worsening discomfort, functional limitation, and work absenteeism.El trabajo a distancia generó procesos de organización y adaptación de los lugares de trabajo, con presencia de factores de riesgo ergonómicos y psicosociales que podrían provocar la aparición de síntomas musculoesqueléticos. El estudio identifica molestias musculoesqueléticas, evalúa el nivel de riesgo asociado al ámbito laboral, estima la necesidad de actuación y las asociaciones existentes en los docentes universitarios que realizaron trabajo remoto debido a la pandemia del COVID-19. El estudio contó con diseño cuantitativo, observacional, transversal y fuente de información secundaria, con análisis estadístico a través del software Jamovi. Los profesores reportaron molestias en el cuello, seguido de la región dorsal o lumbar; se encontró asociación estadísticamente significativa entre la categoría “requiere acción” con aquellos que relataron dedicación a actividades ocupacionales > 8 h/día. Se concluye que el trabajo en casa realizado por los profesores estuvo relacionado con molestias en el cuello y región dorsal o lumbar; la evaluación de riesgos muestra que en esas condiciones los profesores requerían una actuación oportuna para evitar que se agudizaran las molestias, la limitación funcional y el ausentismo laboral.